The Effect of Local Therapy on M1c Prostate Cancer Patients: A Systematic Review and Meta-Analysis - Wang, Zhenghao; Cao, DeHong; Wei, Wuran (Frontiers in Surgery, 2021)
BACKGROUND: A systematic review and meta-analysis was conducted to explore the effect of local treatment (LT) on overall survival (OS) and cancer-specific mortality (CSM) for patients diagnosed with M1c prostate cancer (PCa). METHODS: PubMed, Web of Science, Embase, EBSCO, and Cochrane library databases (updated November 2020) were searched for studies assessing the effect of LT on patients with M1c Pca. The search strategy and study selection process was managed according to the PRISMA statement. RESULTS: Four cohort respective studies were identified for satisfying the inclusion criteria. Our results indicated that LT significantly improved CSM (HR =0.36, 95% CI = 0.22–0.60; P < 0.0001) and OS (HR =0.42, 95% CI = 0.24–0.77; P=0.004). Subgroup analysis showed that radical prostatectomy (RP) and radiation therapy (RT) including brachytherapy (BT), conformal radiation therapy (CRT) and intensity modulated radiation (IMRT) had a significant benefit on cutting down the CSM of M1c PCa patients (HR =0.27, 95% CI =0.13–0.56; P=0.0005 and HR =0.42, 95% CI = 0.20–0.89; P =0.02). In addition, RP had improved the OS for patients (HR =0.33, 95% CI = 0.15–0.73; P=0.008). There was no difference of OS in patients that underwent RT (HR =0.58, 95% CI = 0.24–1.40; P=0.23). No significant heterogeneity was among the results, indicating consistency in the study. CONCLUSIONS: Present meta-analysis indicates that LT for M1c PCa correlated with decreased CSM and enhanced OS. The survival benefit of RP was successfully confirmed and the advantage of RT seemed to be associated with the tumor burden and method of RT.